2016
DOI: 10.1111/jfbc.12302
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Environmental Variation in Chemical Constituents and Antioxidant Properties inRoscoea proceraWall

Abstract: Roscoea procera is an important Himalayan medicinal plant known for its food and medicinal potential due to antioxidant activity. Among its wild populations, total phenolic and flavonoid content in the rhizomes varied significantly (P < 0.05). RP-HPLC analysis of phenolic compounds revealed high variation (P < 0.05) among populations in gallic acid, catechin and p-coumaric acid content. Antioxidant activities determined by different in vitro assays, (ABTS, DPH and FRAP assays) showed the antioxidant potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In view of its significance in the Ayurvedic medicinal system, substantial pharmacological and phytochemical works have not been carried out. Previous phytochemical studies on R. purpurea have described the isolation of two principal groups of compounds: steroids and phenolic derivatives (Misra et al, 2015 ; Srivastava et al, 2015 ; Rawat et al, 2016 ). To date, only a few compounds have been identified and quantified through high-performance liquid chromatography (HPLC) analysis from tubers of this plant by Singh and co-workers, and they are presumed to be associated with its potent antioxidant activity (Gopal et al, 2014 ; Rawat et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of its significance in the Ayurvedic medicinal system, substantial pharmacological and phytochemical works have not been carried out. Previous phytochemical studies on R. purpurea have described the isolation of two principal groups of compounds: steroids and phenolic derivatives (Misra et al, 2015 ; Srivastava et al, 2015 ; Rawat et al, 2016 ). To date, only a few compounds have been identified and quantified through high-performance liquid chromatography (HPLC) analysis from tubers of this plant by Singh and co-workers, and they are presumed to be associated with its potent antioxidant activity (Gopal et al, 2014 ; Rawat et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few compounds have been identified and quantified through high-performance liquid chromatography (HPLC) analysis from tubers of this plant by Singh and co-workers, and they are presumed to be associated with its potent antioxidant activity (Gopal et al, 2014 ; Rawat et al, 2014 ). Alcoholic extracts of the plant have shown in vitro anti-cancer (Srivastava et al, 2015 ), antioxidant (Rawat et al, 2016 ), and immunomodulatory activities (Sahu et al, 2010 ). In our preliminary pharmacological study, cytotoxic activity was found for the methanol extract of R. purpurea against lung cancer cell line at IC 50 25.71 (μg/ml).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in the levels of active principle amongst the populations collected from different locations have been reported earlier in many plant species (Bagdonaite et al 2010;Chaves et al 2013;Filippini et al 2010;Nadeem et al 2000Nadeem et al , 2007Soni et al 2015;Rawat et al 2016) including B. monnieri (Naik et al 2012). Naik et al (2012) have studied variations in bacoside A content in the samples collected from different populations growing in a limited area of the homogenous environment from the state of Karnataka in India.…”
Section: Resultsmentioning
confidence: 81%
“…These populations were evaluated from the samples collected from different regions thus, the observed results could also be due to environmental and edaphic factors (Rawat et al 2016;Cirak et al 2007). A close perusal of literature revealed no report studying the variations in harvestable biomass and levels of bacoside A during different seasons in various populations of B. monnieri collected from different agro climatic zones after these has been maintained at a common location for 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…Similar kind of trends also reported in Guava 32 and Roscoea procera. 33 Elsewhere, studies also indicated that phenolics are positively correlated with antioxidant activity 34,35 and responsible for the maximum activity. …”
Section: Relationship Of Attitudinally Different Sites and Analyzed Pmentioning
confidence: 99%